Plasma endothelin-1 concentrations in patients with retinal vein occlusions. Issue 5 (1st May 1998) - Iannaccone, Alessandro; Letizia, Claudio; Pazzaglia, Sebastiano; Vingolo, Enzo M; Clemente, Giovanni; Pannarale, Mario R
Abstract : AIMS: To investigate whether plasma levels of endothelin-1 (ET-1), a potent vasoconstricting peptide that is crucial in regulating retinal blood flow, were elevated in patients with retinal vein occlusion (RVO). METHODS: ET-1 plasma concentrations were determined by radioimmunoassays in a double blind fashion in a group of 18 selected patients with RVO, in 20 healthy age matched non-smoking, normoglycaemic, normotensive control subjects, and in 15 patients with uncomplicated essential hypertension in the same age range. RESULTS: Patients with RVO had significantly increased ET-1 plasma levels (14.22 (SD 4.6) pg/ml) compared with both normal subjects (7.90 (1.6) pg/ml; p < 0.05) and hypertensive patients (8.50 (2.9) pg/ml; p <0.05). The highest concentrations of circulating ET-1 were found in patients with RVO of the ischaemic type (16.97 (3.5) pg/ml; p < 0.01; n = 7). Systemic hypertension alone did not account for the observed increase in plasma ET-1 concentrations. CONCLUSIONS: These findings raise the possibility that the increased circulating ET-1 levels in patients with RVO may be a marker of the occlusive event, thereby suggesting that ET-1 homeostasis may be relevant to RVO pathogenesis and retinal ischaemic manifestations.